Rapid Establishment of a Cold Chain Capacity of –60°C or Colder for the STRIVE Ebola Vaccine Trial During the Ebola Outbreak in Sierra Leone. (18th May 2018) - Jusu, Morrison O; Glauser, Geoffrey; Seward, Jane F; Bawoh, Mohamed; Tempel, Judith; Friend, Michael; Littlefield, Daniel; Lahai, Michael; Jalloh, Hassan M; Sesay, Amara Bangali; Caulker, Amanda F; Samai, Mohamed; et al.
Abstract: In response to the 2014‒2015 Ebola virus disease (Ebola) epidemic in West Africa, researchers accelerated the development of Ebola vaccines. The Centers for Disease Control and Prevention, in collaboration with local partners, sponsored a phase 2/3 trial in Sierra Leone of a single dose (2 × 10 7 plaque-forming units/mL) of a candidate replication-competent recombinant vesicular stomatitis virus–Zaire Ebola virus envelope glycoprotein vaccine (rVSVΔG-ZEBOV-GP). Because of its early development status and limited, critical stability data, the vaccine had to be stored at –60°C or colder. Planning for the trial began in late 2014 on an accelerated timeline with significant challenges, including the lack of –60°C or colder vaccine storage, handling, and transport capability in a country with high year-round ambient temperatures. The supply chain needs for vaccine handling from storage through transport, up to the time of administration, were carefully evaluated, and then the supply chain was designed. Critical equipment that was procured, shipped, installed, and qualified to meet an aggressive timeline for launching the trial included ultracold freezers, custom-developed Arktek DF containers for storage at –60°C or colder, insulated containers for storage at 2°C–8°C, and multiple backup power sources at vaccine storage sites. Local personnel were trained in good clinical practices and trial documentation. During 9 April–12 December 2015, the trial staff vaccinated approximately 8000 participants. Five temperature excursions occurred, but the vaccine manufacturer assessed that vaccine quality was not impaired because of improper storage or transport temperatures. Both the infrastructure and the human capacity developed for the cold chain during the trial will continue to be useful as the country maintains preparedness for ring vaccination responses and future clinical research. Clinical Trials Registration: ClinicalTrials.gov [NCT02378753] and Pan African Clinical Trials Registry [PACTR201502001037220].